Pemberdayaan UMKM Melalui Digitalisasi Pemasaran dan Penguatan Potensi Desa di Desa Laut Tador, Kabupaten Batu Bara - Sarwoto, Sarwoto; Kadariah, Siti; Nursaimatussadiya, Nursaimatussadiya; Sinaga, Eka Mayastika; Fitrianingsih, Fitrianingsih; Wahyudi, Dani Agus; Sari, Tri Widya; Fadilla, Naila; Camelia, Antis (Community Service Progress, 2025)
The Community Service Program (KKN) is a form of community service conducted in Laut Tador Village, Batu Bara Regency. The main objective of this program is to address issues faced by the community, particularly limited knowledge of business management and product marketing for MSMEs, as well as environmental management. Implementation methods used include observation, coordination with village officials, direct mentoring of MSMEs, outreach, and community activities such as mutual cooperation. The main outcomes of this program are: 1) Three local MSMEs (Palm Palm Sugar, Palm Palm Sugar, and Etawa Goat Milk) were successfully developed through the creation of new packaging, logos, promotional banners, and location registration on Google Maps to expand market reach. 2) Environmental awareness was increased through the installation of educational waste signs and the provision of separate trash bins at SDN 06 Laut Tador. 3) Village potential was strengthened by installing signs indicating tourist directions to Lake Laut Tador. 4) The establishment of a Family Medicine Garden (TOGA) to increase public health awareness. These activities have had a positive impact on MSME independence and village community awareness.